Charles Barbier: A hidden story - Campsie, Philippa (Disability Studies Quarterly, 2021)
Charles Barbier (1767–1841), who invented raised-point writing and the tools for creating it, is remembered today only as a precursor of Louis Braille. Stories of his life and work are mainly variations on two accounts, one by Alexandre-René Pignier published in 1859 and one by Pierre Henri in 1952. The former misrepresented the relationship between Braille and Barbier and the latter hypothesized how Barbier might have developed his ideas and introduced them to Institution Royale des Jeunes Aveugles in Paris. These two accounts have distorted modern ideas about the invention of point writing and the role played by Braille. The author's study of Barbier's correspondence and publications shows that (1) the method that inspired Louis Braille was never intended for the military but was specifically designed for blind people; (2) Barbier did not demonstrate it at the Institution Royale des Jeunes Aveugles; (3) it was not used at the school in a phonetic version; and (4) Barbier and Braille met only after Braille had published his own system. These findings, drawn from primary documents, make it possible to draw a more accurate picture of the original inventor of the method and tools of point writing for people with visual impairments and thereby a more accurate picture of Braille's own achievements.